Measurement of the concentrations of fluorine in the soil of different areas of Savar and its effects on Environment - Molla, Md. Anisur Rahaman; Haque, A.K.M. Fazlul; Haq, Kazi Md. Fazlul (BRAC University, 2010)
To find out the concentration of Fluorine, soil samples were collected from ten different agricultural lands of different places of Savar which were measured by using proton induced gamma rays emission (PIGE) technique. The samples were irradiated by 2.5MeV proton beam from 3MV Van de Graaff accelerator of Bangladesh Atomic Energy Commission (BAEC). Characteristic gamma rays emitted from the exited nuclei of fluorine in the samples were detected by using a high purity germanium (HPGe) detector. Concentrations of the element were measured by PIGE gamma yields with that of USGS geological standards, AGV-1 and Soil-7. The present investigation showed that the concentrations of fluorine in a few samples were under optimum range and most of them were outside of the optimum range; i.e., 200ppm-300ppm. The average concentration of fluorine in the soils of Savar was 787.25ppm which was more than twice its optimum concentration of it in soil. This extra fluorine might be the result of unwise waste management of different industries and laboratories which are located in that area. The concentrations in the soils were compared with that of standard and discussed in both biological and environmental contexts.